Comparative Effects of Covid-19 Pandemic on Agricultural Production and Marketing in Nigeria (Global Journal of Science Frontier Research, 2020)
As the global population decreases due to the Covid-19 pandemic and possible hunger in most developing countries of the world, it is noteworthy to say animal products suffer consumption as an average individual just wants to survive without considering the nutritional requirement of the body system for functionality and production. Humanity has observed various pandemics throughout history, where some of them were more disastrous than the others to humans. We observe a very hard time once again fighting an invisible enemy; the novel COVID-19 (stay home, stay safe slogan). The nationwide lockdown in the country has revealed the various lacunae in the agricultural marketing system; supply chain disruptions exposed critical infrastructure gaps and governance issues regarding the competitiveness of Nigeria's agricultural sector. Many poultry farmers across the country have suffered severe losses due to the COVID-19 pandemic control measures imposed by the government. The situation has impacted their livelihoods negatively, with many closing down their businesses.
Keywords: agriculture; marketing; pandemic; production; covid-19